Co-Constructing Multidisciplinary Coherence in Subject Teacher Education: Students’ Reflections in Group Discussions - Roiha, Anssi; Heinonen, Pilvi (Springer VS, 2025)
This article examines how disciplinary coherence is (co)constructed at the student-oriented level in pedagogical studies at the University of Turku. Based on group discussion data, we analyze how coherence is (co)constructed in planning a mutual multidisciplinary learning module on the topic of sustainable development. The focus is on how students talk about their own discipline and its specific nature in relation to other disciplines and the multidisciplinary modules. From the perspective of (co)constructing coherence in relation to multidisciplinary modules, three different types of coherence building discourses were identified from the data. It was interesting how, on the one hand, one’s own discipline and subject boundaries seem to be valued, and on the other, how this subject-orientation is questioned and seen as problematic. Based on our findings, we discuss how the participants’ discourses of multidisciplinarity relate to the conceptualization of different dimensions of disciplinary coherence (i.e., inter-, multi- and transdisciplinary) and what this means for the development of teacher education.
Coherence in European Teacher Education : Theoretical Models, Empirical Studies, Instructional Approaches